2014
DOI: 10.1007/s00216-014-7628-8
|View full text |Cite
|
Sign up to set email alerts
|

A new rotating-disk sorptive extraction mode, with a copolymer of divinylbenzene and N-vinylpyrrolidone trapped in the cavity of the disk, used for determination of florfenicol residues in porcine plasma

Abstract: A novel extraction approach was developed based on rotating-disk sorptive extraction (RDSE). In this approach the rotating-disk extraction device consists of a Teflon disk, with a cavity that is loaded with a commercial sorbent phase selected according to the polarity of the analyte. To avoid leakage of the sorbent, the cavity is covered with a fiberglass filter and sealed with a Teflon ring. The proposed novel analytical RDSE technique was used in this study to determine florfenicol levels in plasma as a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The extraction device used in RDSE contains a cavity into which the sorptive phase is loaded to extract the analyte from complex samples. 13,14 By following this approach, in this work, we demonstrated that this extraction platform is equally applicable for determination of TCB as its metabolites sulphone and sulphoxide in cattle plasma. This method results in a greener and simpler alternative compared with methods based on SPE.…”
Section: -8mentioning
confidence: 89%
See 1 more Smart Citation
“…The extraction device used in RDSE contains a cavity into which the sorptive phase is loaded to extract the analyte from complex samples. 13,14 By following this approach, in this work, we demonstrated that this extraction platform is equally applicable for determination of TCB as its metabolites sulphone and sulphoxide in cattle plasma. This method results in a greener and simpler alternative compared with methods based on SPE.…”
Section: -8mentioning
confidence: 89%
“…Taking into account our previous experiences in RDSE procedures, 13,14,18,19 the rotation velocity of the disk was kept at 2000 rpm, and all the optimization was made in absence of matrix modifiers. Rotation velocity was kept at the maximum velocity achieved by the magnetic stirrer, because under this condition the boundary layer formed on the surface of the sorptive phase decreases and analyte mass transfer is faster.…”
Section: Optimization Of Variablesmentioning
confidence: 99%
“…As a result, no significant influence was obtained in the areas obtained for the analytes, which is why it was decided to work without the addition of NaCl. Other results indicate that the extraction of compounds of high and medium polarity increases in the presence of salts due to the salting out effect ( Cañas et al., 2014 ; Corrotea el at., 2016 ). The optimized values for the extraction of the seven triazines were pH: 8, Sample volume (mL): 25.0, elution volume (mL): 4.0, amount of adsorbent material (mg): 25, extraction time (min): 100, elution time (min): 5, stirring speed (rpm): 1200.…”
Section: Resultsmentioning
confidence: 99%
“…Richter et al proposed an evolution of the classic RDSE in order to exploit this characteristic. In this case, a cavity is dug into the unit and finally loaded with polymeric sorbent (HLB) particles ( Figure 10B) [63]. The cavity is covered with a filter to confine the particles, avoiding their losses during the extraction.…”
Section: Stir Disk Extractionsmentioning
confidence: 99%